Perswazyjność przekazu a problem legitymizacji władzy - Leśniczak, Rafał (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2016)
The author analyses several selected speeches of Italian politicians: the founder of the Forza Italia party, Silvio Berlusconi; founder and leader of the Movement Five Stars, Beppe Grillo; and the current Prime Minister of Italy, Matteo Renzi. The study makes it possible to evaluate whether the conditions for the ideale Sprechsituation of Jürgen Habermas is fulfilled in analysing public discourse. Particular attention will be given to the relationship between the persuasiveness of communication and the problem of legitimacy.